Comparative Study of Different Yield Stimulation Systems on Young Trees of Hevea Clone RRIM 901 Panel Bo-1 - Md. Said, Mohd Akbar (2003)
The emphasis of the study is to evaluate the response of young Hevea trees to a new method of stimulation, REACTORRIM technique, developed by the Rubber Research Institute of Malaysia (RRIM) in 1990. The main objective of the development of REACTORRIM method of stimulation is to address the problem of shortage of skilled tappers to tap trees according to the conventional tapping system. REACTORRIM technique, which employs a concept of direct supply of ethylene into the laticiferous tissue at a slow but continuous rate, is effective for increasing the yield response of premium and old rubber trees. Young Hevea trees clone RRIM 901, panel BO-1 responded negatively to the method of stimulation irrespective of methods of latex extraction, age of tree and history of tapping. The results showed that the negative effects were seen earlier on the cut systems than on the puncture tapping system. The bole growth quantified during the study period was shown not to be solely the manifestation of cambial activity but also the continuous formation of layers of unproductive dry tissue. Despite severe bark reaction, the puncture tapping system responded more favorably to the REACTORRIM technique. All the experiments showed a consistent trend, where a higher dosage of ethylene was required for the puncture tapping system. The results confirmed the inverse relationship between dosage of ethylene and number of latex vessels severed during tapping. The effect of methods of stimulation on the status of elements and selected physiological parameters was markedly observed. Removal of nutrients was higher in the REACTORRIM stimulated trees. The high removal of nutrients and low content of sucrose can be associated with the downward trend of yield of the Hevea trees used. There was no significant difference between the status of nutrients during the moderate and high yielding periods of the year. Sucrose appeared as the most suitable parameter to be used as stress indicator for young Hevea trees, clone RRIM 901, panel BO-1 used in this study. The content of sucrose was influenced by the interaction effect between the methods of stimulation and latex extraction. The content of sucrose of the REACTORRIM stimulated treatments was consistently lower than the non-REACTORRIM stimulated treatments, except for the puncture tapping system.Young Hevea trees clone RRIM 901, panel BO-1 used in the study responded negatively to REACTORRIM method of stimulation with drastic reduction in latex production, low content of sugar, high incidence of tapping panel dryness and considerably high loss of nutrient from latex and after-shaved bark. The yield profile obtained from the study showed that there was no sign of yield recovery indicating collapse of lactiferous system and impaired biosynthetic processes. Findings established from the study confirmed that REACTORRIM technique is not suitable as yet, for commercial uptake on young Hevea trees. For young Hevea trees, the most suitable exploitation system is the conventional 1/2S d/3 system with or without mild ethephon stimulation.